Second Five Year Plan Kerala - Planning Commission (Planning Commission, 1958)
Kerala State has been formed by the union of the major part of the old Travancore-Cochin State (the taluks of Thovala, Agastheeswaram, Kalkulam, Vilavancode and a part of Shencottah being transferred to the Madras State) and the Malabar district and Kasaragod taluk of the old Madras State. It stretches along the shores of the Arabian Sea for a distance of about 360 miles with Mysore State on the north and north-east and Madras State on the east and south. The breadth of the State varies from 20 miles in the extreme north and south to over 75 miles in the middle. the area of the State is nearly 15,000 square miles.
Government of Kerala